Implementation of the Ministry of Education and Culture's Independent Campus Learning Program (MBKM) Policy at Universitas PGRI Wiranegara - Yuniar Mujiwati; Mohamad Rifqi Hamzah; Daryono Daryono; Innayatul Laili (CV. AFDIFAL MAJU BERKAH, 2023)
The MBKM Program Policy provides ample space for students to acquire knowledge at tertiary institutions in a flexible manner. It not only requires them to attend lectures in a classroom setting but also allows them to gain knowledge and skills based on their competencies through the developed programs. The Merdeka Campus (MBKM) was officially launched in early 2020 by the Minister of Education and Culture through several regulations. Uniwara, as a tertiary institution, has been actively involved in MBKM activities since 2020. The implementation of MBKM at Uniwara began with the formulation of policies and the issuance of regulatory decrees by the Chancellor of Uniwara. The implementation process of MBKM involves authorized academic officials, namely the Chancellor, Deputy Chancellor for Academic Affairs, the Dean, and the Head of Study Program, all aiming for the successful implementation of the MBKM policy at Uniwara. This research utilizes a qualitative method with a descriptive approach to provide a comprehensive understanding of the Implementation of the Independent Learning Campus policy of kemendikbudristek at Uniwara. In conducting the research, the authors gather various kinds of information relevant to the discussed topics